The Role of Chromatin Remodeling Enzymes in Prevention of CAG-Repeat Expansions. - Walsh, Stephen C. (Tufts Archival Research Center, 2014)
Expansions of CAG repeats, often caused by errors in DNA replication, repair, and recombination, can cause neurodegenerative diseases. However, organisms can employ a number of strategies in preventing genomic instability. Previous data in our lab suggests that acetylation of lysine residues H4-K12 and H4-K16 at CAG repeats is important in marking the DNA for repair, but the exact molecular mechanism of how these modifications affected repair fidelity remained unknown. This thesis explores the action of chromatin remodelers, hypothesized to be directly recruited to the acetylated residues through their bromodomain protein motif. Our data support that recruitment of the bromodomain-containing remodeling proteins Rsc2 and Bdf1 by the acetylation of H4-K16 facilitates DNA repair through a post-replicative repair pathway via gap-induced sister chromatid recombination (SCR). Additional evidence presented here identifies that this feature is unique to histone H4, and that CAG repeat maintenance is not affected by the acetylation state of other histone residues. By contributing data from this thesis with previous work in our lab, a novel model of dynamic H4 acetylation leading to high-fidelity DNA repair at CAG repeats has been elucidated.